Development of a Nanostructured Electrochemical Genosensor for the Detection of the K-ras Gene - Luis Fernando Garcia-Melo; Miguel Morales-Rodríguez; Eduardo Madrigal-Bujaidar; Eduardo O. Madrigal-Santillán; José Antonio Morales-González; Rosa Natali Pineda Cruces; Jorge Alfredo Campoy Ramírez; Pablo Damian-Matsumura; Alexandro Tellez-Plancarte; Nikola Batina; Isela Álvarez-González (Journal of Analytical Methods in Chemistry, 2022)
In the scientific literature, it has been documented that electrochemical genosensors are novel analytical tools with proven clinical diagnostic potential for the identification of carcinogenic processes due to genetic and epigenetic alterations, as well as infectious diseases due to viruses or bacteria. In the present work, we describe the construction of an electrochemical genosensor for the identification of the k12p.1 mutation; it was based on use of Screen-Printed Gold Electrode (SPGE), Cyclic Voltammetry (CV), and Atomic Force Microscopy (AFM), for the monitoring the electron transfer trough the functionalized nanostructured surface and corresponding morphological changes. The sensitivity of the genosensor showed a linear response for the identification of the k12p.1 mutation of the K-ras gene in the concentration range of 10 fM to 1 μM with a detection limit of 7.96 fM in the presence of doxorubicin (Dox) as DNA intercalating agent and indicator of the hybridization reaction. Thus, the electrochemical genosensor developed could be useful for the identification of diseases related with the K-ras oncogene.